ASSESSMENT OF PUBLIC ADMINISTRATION OF UKRAINE BASED ON THE BASIC PRINCIPLES OF PERFORMANCE - ARTEMOV, Serhii; MUZHYCHENKO, Yevhen; DOVHOPOL, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article evaluates the public administration of Ukraine according to the basic principles. It is established that public administration is a system of organization and management of Public Affairs, which includes the processes of planning, implementing and evaluating policies and programs related to public needs. It covers the activities of state bodies, Local Self-Government, as well as other institutions that ensure the performance of state functions and the provision of public services. Public administration assessment is an important process and allows you to understand how effectively public policies and programs are being implemented, as well as whether the goals set are being achieved. Analysis of the performance of public organizations helps to identify weaknesses and opportunities for improving the quality of public services. Evaluation helps to increase the accountability of public authorities to citizens, since the results of the evaluation can be used to report on the work done. The evaluation process may involve engaging citizens to discuss the results, which increases transparency and trust in public institutions. An assessment of Public Administration can indicate the need for reforms that allow adapting management practices to changes in society and the economy. The results of the assessment can serve as a basis for developing new strategies and policies that meet the current needs of society. Thus, public administration assessment is an important tool for ensuring its effectiveness, accountability, and adaptability to change. In the context of Ukraine, public administration faces numerous challenges, such as corruption, lack of transparency, and the need for reform to improve the efficiency and quality of service delivery.